The hepatitis C cascade of care in the Belgian HIV population: One step closer to elimination. (April 2021) - Busschots, Dana; Kremer, Cécile; Koc, Özgür M.; Heyens, Leen; Bielen, Rob; Apers, Ludwig; Florence, Eric; Messiaen, Peter; Van Laethem, Kristel; Van Wijngaerden, Eric; Nevens, Frederik; Hens, Niel; et al.
Abstract: Objectives: The Belgian population of people living with HIV (PLHIV) has unrestricted access to direct-acting antiviral (DAA) treatment for hepatitis C virus (HCV) infection, since 2017. International literature claims that half of the patients remain untreated in high-income countries with unrestricted access to DAA. This study was initiated to provide an overview of the present situation in Belgium and recommendations for HCV care in PLHIV in other regions. Methods: This was a retrospective, multicenter study of PLHIV in Belgium, from January 1, 2007 to December 31, 2018. The HCV cascade of care was examined. Results: Out of 4607 unique PLHIV, 322 (7.0%) tested positive for HCV antibody and HCV RNA positivity was seen in 289 (6.3%). Of those with a proven HCV infection, 207/289 (71.6%) initiated treatment. Of the 171 (82.6%) persons with a sustained virologic response (SVR), 16 (9.4%) subjects were reinfected. Conclusions: We present a care cascade of 4607 PLHIV in Belgium. Treatment initiation and SVR rates were high compared to other regions. Implementation of a national HCV register to track progress and yearly screening, especially in PLHIV with high-risk behavior, remains crucial. Identifying reasons for not initiating treatment is necessary to achieve elimination of HCV in PLHIV by 2030.